Identifying the Top Ten Unanswered Questions in Community Nursing: A James Lind Alliance Priority Setting Partnership in Community Nursing - Catherine Henshall; Louise Jones; Claire Armitage; Lee Tomlinson (Hindawi Limited, 2022)
Community nurses deliver comprehensive nursing care to patients living outside of hospital settings and play a crucial role in meeting individual and public health needs. Research is essential in providing evidence-based care for patients; however, most community nurses are not research active, with few relevant studies and little funding for community nursing research. To address this, four National Institute for Health Research senior nurse researchers in England conducted a James Lind Alliance priority setting partnership in community nursing with the aim of raising the international profile of community nursing research through the identification of meaningful research priorities that matter to this community. Community nurses, patients, and carers were integral to the process, which aimed to identify the top ten unanswered questions to inform community nursing practice. The Priority Setting Partnership process utilised a coproduction, mixed-methods approach. It involved consultation meetings with stakeholder partners and nested quantitative surveys. The study ran from March 2020 until September 2021, and numerous unanswered evidence uncertainties were identified. The top ten priority questions included nursing and patient focussed issues, which reflect the complexity of care delivered to patients and the workforce pressures community nurses face. Findings reflect the views of community nurses, patients, and carers and highlight areas that need attention to ensure research is embedded within community nursing settings. Identification of the top ten priorities has provided an international platform for community nursing research. This must be sustained through engagement, collaboration, funding, and innovation and has widespread implications for developing the community nursing workforce and optimising the safety and quality of patient care.